Morphological variability and taxonomic affinity of cocoa (Theobroma cacao L.) clones from Central Sulawesi, Indonesia - Widaysary, Rarastyan Arum; Susandarini, Ratna (Current Botany, 2020)
Cocoa (Theobroma cacao L.) is one of the most important export commodities of Indonesia, with Sulawesi becomes the largest cocoa production centers in Indonesia. Since the majority cocoa production comes from Sulawesi Island, there is high diversity of cocoa clones cultivated in this area. The objective of this study was to explore morphological variability and to assess taxonomic affinity of cocoa clones cultivated by smallholder farmers in four districts of Central Sulawesi, Indonesia. Nineteen cocoa clones from the districts of Sigibiromaru, Palolo, South Parigi and Sausu were used in this study. Fourteen morphological characters of leaves, fruits, and beans were examined. Cluster analysis were done to determine taxonomic affinity between the clones. Results of this study indicated that there was high morphological variability, mainly in fruit or pod characters. Cluster analysis on 14 morphological characters resulted in the grouping of the clones into two main clusters. The grouping of cocoa clones did not correspond to the geographical origin of samples. It is concluded that taxonomic affinity was determined by similarities of morphology, especially fruit and bean characters.